(untitled) (Research, Society and Development, 2021)
The creation of public policies had an important meaning in the generation of innovations, in the development and a better life condition of the families of the rural environment. As a microcredit policy, AgroAmigo was conceived in the ideal of further democratizing credit to the portion of the rural population that does not have access to banking services, contributing to the reduction of social exclusion and serving as a tool aimed at rural people in the sense to contribute to the departure of thousands of family farmers from the poverty zone and even destitution, allowing those without capital to have access to subsidized financial resources, in a targeted and participatory way. In this context, this study aimed to describe the Agroamigo program and its importance for the local economy, analyzing the evolution and functionality of this program for the development of family farming. The present work is of a basic research nature, where the objective is to generate new knowledge useful for the advancement of science and which does not demand immediate application of it. The technical procedures adopted that best contribute to the results of this research are bibliographic and documentary. According to the above, it can be concluded that the Agroamigo Program has made a significant contribution to the quality of life of families benefited through family farming, enabling small farmers to be served in their own localities so that they do not need to. moving to agencies, in addition to having specialized monitoring and guidance in rural activities.